Law Enforcement Against The Perpetrator of Physical Violence in The Healthcare Service Environment - Novian Kurnia Perkasa (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2023)
Health workers often experience physical violence in carrying out their work. The research aims to determine the extent to which legal protection applies to health workers. The data used in this research was taken from several hospitals and other health services. The method used is a case study with a qualitative approach involving several parties involved in implementing legal protection for health workers. Legal protection for health workers who experience physical violence while working in health services is regulated in several laws, namely Law Number 36 of 2014 concerning Health, Law Number 29 of 2004 concerning Medical Practice, Law Number 38 of 2014 about health. Nursing, Law Number 4 of 2014 concerning Midwifery. Apart from that, there are still many obstacles and challenges in its implementation. In conclusion, legal protection for health workers who experience physical violence in carrying out their duties in the health service environment is very important and must be provided firmly.